Pengaruh Profitabilitas, Leverage, dan Likuiditas Terhadap Financial Distress - Salwa Latifa Putri; Ai Hendrani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Financial distress occurs when a company is unable to meet its financial obligations within a predetermined period of time. This study was conducted with the aim of knowing how profitability, leverage, and liquidity in the retail trade sub-sector industry listed on the Indonesia Stock Exchange (IDX) can have an impact on the state of the company against potential financial distress. This study tries to determine the cause-and-effect relationship between the influenced factor (dependent variable) and the influencing factor (independent variable) known as causality. then emphasizes the use of multiple linear regression analysis to focus on the formation of the equation model. This research design utilizes secondary data sources indirectly from financial reports available on the Indonesia Stock Exchange (IDX) through its official website at www.idx.co.id and also through the official web pages of related entities. This research uses non-probability selection techniques with a purposive sampling approach, finding 12 companies and a total of 48 samples that meet the research criteria in the retail trade sub-sector for the 2019-2022 period. Profitability and liquidity have a significant negative effect on financial distress, while leverage has a significant positive effect on financial distress.